Selection of single domain antibodies against the CD20 receptor: a new treatment with potencial anti-tumor properties for B-cell malignancies - André, Ana Filipa Santos (2016)
Tese de mestrado, Biologia Molecular e Genética, Universidade de Lisboa, Faculdade de Ciências, 2016